Effect of aripiprazole as an adjunct to atypical antipsychotics on weight and metabolic profile: a 12-week open-label trial. (October 2021) - Gupta, Bhanu; Chee, Kok-Seng; Neo, Li-Qi; Tang, Charmaine; Hariram, Jayaraman; Tan, Geoffrey Chern-Yee; Verma, Swapna; Basu, Sutapa; Appan, Deva-Priya; Ting, Chan-Chun; Abdin, Edimansyah; Lee, Jimmy
Background: Atypical antipsychotics are widely prescribed, yet have been associated with weight gain and metabolic syndrome. Aim: To study the effect of adjunct low-dose aripiprazole on weight and metabolic parameters of subjects on atypical antipsychotics (olanzapine, clozapine or risperidone). Methods: The study was carried out as an open-label trial with a fixed dose of 5 mg aripiprazole added to the patient's current antipsychotic for 12 weeks. The primary outcome measure was mean change in weight, while secondary outcome measures included change in waist circumference; fasting blood glucose; HbA1c; triglycerides; total, HDL and LDL cholesterol levels; functioning; and neurocognition. Results: For the overall study ( n  = 55), there was no significant effect of adjunct aripiprazole on the weight of the subjects. However, the clozapine group achieved significant weight loss ( p  = 0.002) and also had significant improvements in total cholesterol ( p  < 0.001), HDL ( p  = 0.016), LDL ( p  = 0.044) and triglyceride levels ( p  = 0.038). The olanzapine group had significant improvement in triglycerides ( p  = 0.001), and other metabolic parameters for this group showed improvement trends, but did not reach statistical significance. The risperidone group did not show any significant improvement in weight or metabolic parameters. Conclusions: The study adds support to the adjunctive use of aripiprazole to clozapine for weight loss and improvement in metabolic profile, and for reduction in cardiometabolic risk for patients on olanzapine. Trial Registration: Clinicaltrials.gov identifier: NCT02949752